COFFEE SOMMELIER : A VOYAGE THROUGH CULTURE AND RITES OF COFFEE - Odello, Luigi, 1951-; Ruggieri, Giovanni, 1984-; Petroni, Fabio, 1964- (Milan, Italy : White Star Publishers, 2018)
A simple porcelain cup contains a true treasure consisting of aromas and flavours as well as an age-old history that combines culture and tradition. This book, marvellously illustrated by the photographs of the master of still-life photography Fabio Petroni, is entirely given over to every aspect of coffee and coffee-making and helps readers discover all the secrets of this amazing drink consumed every day by millions of people the world over.
Includes bibliographical references and index.
Keywords: Coffee; Cooking (Coffee).; Coffee -- History